Detection of Luminescence Centers in Colloidal Cd\(_{0.3}\)Zn\(_{0.7}\)S Nanocrystals by Synchronous Luminescence Spectroscopy - Thang, Phi Van; Tuyen, Ho Van; Quang, Vu Xuan; Lieu, Nguyen Thi Thuy; Thanh, Nguyen Trong; Nghia, Nguyen Xuan (Communications in Physics, 2020)
With the advantages of selectivity, spectral resolution and reduction of interference on account of light scattering, synchronous luminescence spectroscopy (SLS) is successfully applied to analyze complex mixtures with overlapped emission and/or excitation spectra. In fact, it is difficult to clearly distinguish the contributions of various luminescence centers to low-energy band of semiconductor nanocrystals (NCs). Herein, we report the application of SLS method to detect luminescence centers in colloidal Cd0.3Zn0.7S NCs. Their conventional luminescence and synchronous luminescence spectra were comparatively investigated. Differently from conventional luminescence spectrum, the emission peaks at 460 and 515 nm were found using SLS method. They are attributed to the emission transitions related to sulfur and zinc/cadmium vacancies. The obtained results are useful to clarify the nature of luminescence centers as well as relaxation mechanism in CdxZn1-xS NCs.